In-situ doped crosslinked polyethylene insulating material and preparation method thereof

By generating nanosilicon dioxide particles in situ in polyethylene, the problem of space charge aggregation of crosslinked polyethylene insulating materials for ultra-high voltage DC cables under high electric fields is solved, and higher DC breakdown strength and production continuity are achieved.

CN119410050APending Publication Date: 2025-02-11SHANGHAI NEW SHANGHUA POLYMER MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411540418.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing crosslinked polyethylene insulating materials for ultra-high voltage DC cables are prone to distortion of space charge aggregation under high electric fields, resulting in the cable being easily broken down, and the inorganic nano-doping modification has poor dispersion and filter clogging.

Method used

By generating nanosilicon dioxide particles in situ in polyethylene, hydrolysis and polycondensation are performed using ethyl orthosilicate, space charge aggregation is suppressed, and the problem of poor dispersion of inorganic powders is avoided.

Benefits of technology

It effectively suppresses the accumulation of space charge inside the insulating material, reduces the electric field distortion rate, improves the DC breakdown strength, avoids filter clogging, and improves the production continuity and performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112666740000061
    Figure BDA0005112666740000061
  • Figure BDA0005112666740000071
    Figure BDA0005112666740000071
  • Figure BDA0005112666740000072
    Figure BDA0005112666740000072
Patent Text Reader

Abstract

The invention relates to the technical field of cable materials, and particularly discloses an in-situ doped crosslinked polyethylene insulating material and a preparation method thereof. The invention relates to an in-situ doped cross-linked polyethylene insulating material which comprises the following components in parts by weight: 100 parts of low-density polyethylene and 1.5-2.0 parts of tetraethoxysilane, 1.5-1.7 parts of a cross-linking agent, 0.3 part of an antioxidant, 0.1 part of an anti-scorching agent, 0.02 part of a catalyst and 0.2-0.4 part of a voltage stabilizer. According to the in-situ doped cross-linked polyethylene insulating material disclosed by the invention, in-situ doping is carried out by adding tetraethoxysilane, so that the problem that nano silicon dioxide is difficult to disperse is solved, and the problem of space charge aggregation in the cross-linked polyethylene insulating material under an ultrahigh-voltage direct-current electric field can be more effectively inhibited; in addition, the 4-hydroxythieno [3, 2-c] pyridine is found to be capable of improving the dielectric breakdown strength and other properties of the cross-linked polyethylene direct-current insulating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of cable materials, and more specifically, to an in-situ doped cross-linked polyethylene ultra-high voltage direct current insulation material and a preparation method thereof. Background Art

[0002] Cable insulation materials refer to materials used for cable insulation layers. Their main function is to prevent current leakage and provide protection. Common cable insulation materials include polyethylene, cross-linked polyethylene, polyvinyl chloride, etc. Among them, cross-linked polyethylene has problems such as space charge accumulation and electric field distortion. When used in high-voltage and ultra-high-voltage DC cables (voltage 150kV-500kV), it needs to be modified.

[0003] At present, there are three ways to modify the cross-linked polyethylene insulation material for ultra-high voltage DC cables: One is grafting modification: that is, grafting polar groups on the low-density polyethylene molecular chain to capture space charges. However, due to the complexity of the grafting reaction and the large amount of residual by-products, it is easy to have serious consequences.

[0004] The second is polymer blending modification: blending with polar polymers, but the introduced polar groups will be ionized under high electric fields to produce heteropolar space charges, so the effect is not ideal either.

[0005] The third is inorganic nano-doping modification: by doping nanoparticles such as nano-silicon dioxide, nano-titanium dioxide, and nano-magnesium oxide, the huge amount of space charge generated inside the cross-linked polyethylene during cable operation is suppressed to prevent the cable from being broken down by the distorted electric field. However, because inorganic nanoparticles are easy to agglomerate, the diameter of the aggregates formed may exceed 100μm, which is easy to clog the filter, making it impossible to continue production for a long time. It is also difficult to disperse evenly in cross-linked polyethylene, making it difficult to give full play to its effect of suppressing space charge aggregation, making it difficult to increase the voltage level of the cable, and it will soon be broken down by high voltage and scrapped. Summary of the invention

[0006] In order to suppress the electric field distortion caused by space charge accumulation inside cross-linked polyethylene, the present application provides an in-situ doped cross-linked polyethylene insulating material and a preparation method thereof. By utilizing tetraethyl orthosilicate to in-situ generate nano-silica particles in polyethylene particles, it not only suppresses space charge accumulation but also avoids the problem of poor dispersion of inorganic powders.

[0007] In a first aspect, the present application provides an in-situ doped cross-linked polyethylene insulation material and a preparation method thereof, which adopts the following technical solution: An in-situ doped cross-linked polyethylene insulating material comprises the following components in parts by weight: 100 parts of low-density polyethylene, 1.5-2.0 parts of tetraethyl orthosilicate; 1.5-1.7 parts of cross-linking agent, 0.3 parts of antioxidant, 0.1 parts of scorch retarder, 0.02 parts of catalyst, 0.2-0.4 parts of voltage stabilizer.

[0008] By adopting the above technical solution: adding ethyl orthosilicate, which is an organic liquid and has good compatibility with polyethylene, can be dispersed in situ in polyethylene, hydrolyzed, polycondensed and generate nano-silicon dioxide. This not only inhibits the accumulation of spatial charge inside the insulating material, but also avoids the problem of poor dispersion of inorganic powders, greatly improves the efficiency of nano-silicon dioxide, such as reducing the average spatial charge density of the material; at the same time, it avoids filter blockage during long-term extrusion, and solves the problem of nano-silicon dioxide doped polyethylene insulating material in actual production.

[0009] After testing, when ethyl orthosilicate was added, the average space charge density of the insulating material under a 20kV / mm DC electric field for 60 minutes was 2.1C / m 3 , the electric field distortion rate at 70℃ is 31%, and the DC breakdown strength at 70℃ is 118kV / mm; when an equal amount of nano-silicon dioxide is used instead of tetraethyl orthosilicate, the average space charge density and the electric field distortion rate at 70℃ of the insulating material are increased, and the DC breakdown strength at 70℃ decreases, indicating that tetraethyl orthosilicate significantly improves the insulation performance of the insulating material.

[0010] Optionally, the voltage stabilizer is 4-hydroxythieno[3,2-c]pyridine.

[0011] By adopting the above technical solution: research has found that 4-hydroxythieno[3,2-c]pyridine is significantly better than the common voltage stabilizers currently used in improving the comprehensive insulation performance of materials. According to the test results: when other common voltage stabilizers (n-propylbenzoic acid) on the market are used, the dielectric strength of the insulating material is 118kV / mm; and when the same amount of 4-hydroxythieno[3,2-c]pyridine is used instead of n-propylbenzoic acid, the 70℃ DC breakdown strength of the insulating material is significantly improved to 139kV / mm.

[0012] The reason is that 4-hydroxythieno[3,2-c]pyridine has both 4-hydroxythiophene and pyridine groups, and can be interconverted between enol and keto forms, which can homogenize the internal trap energy levels of polyethylene, increase the trap density, and control charge aggregation. In addition, the substance has a high boiling point, which can solve the problem that the commonly used voltage stabilizers with low boiling points (such as n-propylbenzoic acid, aminoquinoline, aminopiperidines, azos, benzophenones, etc.) are easily volatilized and lost when the cross-linked tube is heated, thereby ensuring the high efficiency of the voltage stabilizer and effectively improving the DC breakdown strength and other properties of the insulating material.

[0013] Optionally, the density of the low-density polyethylene is 0.920 g / cm 3 .

[0014] By adopting the above technical solution: the polyethylene with the above density has good flexibility, moderate crystallinity, good cross-linking agent penetration and absorption effect, and relatively high mechanical strength, which can meet the use requirements.

[0015] Optionally, the cross-linking agent is one or both of dicumyl peroxide and di-tert-butyl peroxide.

[0016] Optionally, the antioxidant is one or more of 2-propenoic acid-2-(1,1-dimethylethyl)-6-[[3-(1,1-dimethylethyl)-2-hydroxy-5-methylphenyl]methyl]-4-tolyl ester, 1,3,5-trimethyl-2,4,6,-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 2-{1-[2-hydroxy-3,5-bis(2-methylbutyl-2-yl)phenyl]ethyl}-4,6-di(2-methylbutyl-2-yl)phenyl acrylate, and β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid n-octadecyl alcohol ester.

[0017] By adopting the above technical solution, the insulating material in the present application has lower requirements on antioxidants, and the performance of the insulating material prepared when the above antioxidants are used is better.

[0018] Optionally, the scorch retarder is one or more of N-cyclohexylthiophthalimide, N-phenyl-N-trichloromethylthiobenzenesulfonamide, and N-nitrosodiphenylamine.

[0019] Optionally, the catalyst is one or both of di-n-octyltin dilaurate and bismuth neodecanoate.

[0020] By adopting the above technical solution: trace amounts of di-n-octyltin dilaurate and bismuth neodecanoate can effectively catalyze the polycondensation reaction of ethyl orthosilicate, thereby ensuring the generation of nano-silicon dioxide.

[0021] Optionally, the catalyst has a free chlorine content of 30 ppm.

[0022] By adopting the above technical solution: controlling the free chlorine content to be less than the above range, it can be ensured that the DC insulation performance of the cross-linked polyethylene insulation material is not affected.

[0023] In a second aspect, the present application provides a method for preparing an in-situ doped cross-linked polyethylene insulating material, using the following technical solution: An in-situ doped cross-linked polyethylene insulation material comprises the following steps: S1. Melt low-density polyethylene, antioxidant, voltage stabilizer, tetraethyl orthosilicate and catalyst at 120-140°C, filter, granulate in water, and dehydrate to obtain modified polyethylene particles; S2. The modified polyethylene particles are reacted at 90-95°C for 2-3h, and then a cross-linking agent and a scorch retarder are added, and the particles are subjected to permeation absorption at 95-98°C for 2-3h, and then devolatilized, dried with a molecular sieve, and cooled to obtain the product.

[0024] By adopting the above technical solution: in step S1, under the combined action of high temperature and catalyst, tetraethyl orthosilicate undergoes hydrolysis and polycondensation reactions successively, thereby forming nano-silicon dioxide in situ in polyethylene, thereby achieving polyethylene modification. In actual production, step S1 is carried out in a BUSS reciprocating single-screw mixer, and most of the reaction by-product ethanol can be discharged from the one-way valve, thereby reducing the by-products remaining in the insulating material and improving the product quality.

[0025] In summary, this application has the following beneficial effects: 1. The present application adopts tetraethyl orthosilicate, which is polymerized in situ in polyethylene to generate silicon dioxide, which can not only inhibit the space charge accumulation inside the high-voltage DC insulating material and reduce the electric field distortion rate at 70°C; at the same time, it avoids the clogging of the filter during the extrusion process caused by the direct addition of silicon dioxide, and solves the problem of nano-silicon dioxide doped polyethylene insulating material in actual production; 2. The present application found that the addition of 4-hydroxythieno[3,2-c]pyridine can act as a voltage stabilizer and improve the performance of the insulating material. Taking the DC breakdown strength as an example, compared with the DC breakdown strength of 118 kV / mm when other common voltage stabilizers are used, the addition of 4-hydroxythieno[3,2-c]pyridine can increase the DC breakdown strength to above 139 kV / mm. DETAILED DESCRIPTION

[0026] The present application is further described in detail below in conjunction with the examples. Among them, ethyl orthosilicate was obtained from Hubei New Blue Sky New Materials Co., Ltd., model D-130; 4-hydroxythieno[3,2-c]pyridine was obtained from Hubei Shixing Chemical Co., Ltd., CAS number 27685-92-3, specification 99%.

[0027] It should be noted that the antioxidant may be one or more of 2-acrylic acid-2-(1,1-dimethylethyl)-6-[[3-(1,1-dimethylethyl)-2-hydroxy-5-methylphenyl]methyl]-4-tolyl ester, 1,3,5-trimethyl-2,4,6,-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 2-{1-[2-hydroxy-3,5-bis(2-methylbutyl-2-yl)phenyl]ethyl}-4,6-di(2-methylbutyl-2-yl)phenyl acrylate, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid n-octadecyl alcohol ester. The scorch retarder may be one or more of N-cyclohexylthiophthalimide, N-phenyl-N-trichloromethylthiobenzenesulfonamide, and N-nitrosodiphenylamine, and the catalyst may be one or two of di-n-octyltin dilaurate and bismuth neodecanoate. The above selection has little effect on the performance of the insulating material. This application only briefly introduces 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, N-cyclohexylthiophthalimide, and di-n-octyltin dilaurate (free chlorine content of 30 ppm, purity of 99%) as examples.

[0028] Similarly, low-density polyethylene can be selected with a density of 0.920-0.924g / cm 3 Low-density polyethylene within the range, this application only takes one of them as an example for brief introduction: density 0.920g / cm 3 The melt flow rate is 2.0g / 10min, the content of opaque impurities is 0 pieces / kg above 50μm, the content of white transparent gel is 0 pieces / kg above 100μm, and 2 pieces / kg between 50-100μm. Example

[0029] Example 1 An in-situ doped cross-linked polyethylene insulating material, the components and amounts of which are shown in Table 1, is prepared by the following steps: S1, adding low-density polyethylene to a BUSS reciprocating single-screw mixer, adding antioxidant 1,3,5-trimethyl-2,4,6,-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, voltage stabilizer n-propyl benzoic acid from the side feed port, adding ethyl orthosilicate from spray gun port 1, adding catalyst di-n-octyltin dilaurate from spray gun port 2, melt mixing at 120° C., filtering through a three-layer dynamic filtration system of 300 mesh, 600 mesh, and 300 mesh, and then introducing into deionized water (conductivity 0.04 μS / cm) for granulation and centrifugal dehydration to obtain modified polyethylene particles; S2. Add the modified polyethylene particles into a heated drum device, react at 90°C for 3 hours, add the cross-linking agent DTBP and the anti-scorching agent N-cyclohexylthiophthalimide, raise the temperature to 95°C for 3 hours of permeation absorption, devolatilize, dry with molecular sieve (control the water content within 100 ppm), and cool naturally to obtain.

[0030] Example 2 An in-situ doped cross-linked polyethylene insulating material is different from Example 1 in that the voltage stabilizer is used differently, and an equal amount of 4-hydroxythieno[3,2-c]pyridine is used instead of n-propylbenzoic acid.

[0031] Example 3 An in-situ doped cross-linked polyethylene insulation material, the components and their amounts are shown in Table 1, and is prepared by the following steps: S1, adding low-density polyethylene to a BUSS reciprocating single-screw mixer, adding an antioxidant 1,3,5-trimethyl-2,4,6,-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and a voltage stabilizer 4-hydroxythieno[3,2-c]pyridine from a side feed port, adding tetraethyl orthosilicate from a spray gun port 1, adding a catalyst di-n-octyltin dilaurate from a spray gun port 2, melt-mixing at 130° C., filtering through a three-layer dynamic filtration system of 300 mesh, 600 mesh, and 300 mesh, and then introducing into deionized water (conductivity 0.04 μS / cm) for granulation and centrifugal dehydration to obtain modified polyethylene particles; S2. Add the modified polyethylene particles into a heated drum device, react at 90°C for 3 hours, then add the cross-linking agent DTBP and the anti-scorching agent (N-cyclohexylthiophthalimide), permeate and absorb at 95°C for 2 hours, devolatilize, dry with molecular sieve (control the water content within 100 ppm), and cool naturally to obtain.

[0032] Example 4 An in-situ doped cross-linked polyethylene insulation material, wherein the components and the amounts thereof are shown in Table 1, is prepared by the following steps: S1, adding low-density polyethylene to a BUSS reciprocating single-screw mixer, adding an antioxidant 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and a voltage stabilizer 4-hydroxythieno[3,2-c]pyridine from a side feed port, adding tetraethyl orthosilicate from a spray gun port 1, adding a catalyst di-n-octyltin dilaurate from a spray gun port 2, melt-mixing at 140° C., filtering through a three-layer dynamic filtration system of 300 mesh, 600 mesh, and 300 mesh, and then introducing into deionized water (conductivity 0.04 μS / cm) for granulation and centrifugal dehydration to obtain modified polyethylene particles; S2. Add modified polyethylene particles to a rotary drum device, react at 98° C. for 2 h, then add cross-linking agent DCP and anti-scorching agent N-cyclohexylthiophthalimide, permeate and absorb at 98° C. for 2 h, devolatilize, dry with molecular sieve (control the water content within 100 ppm), and cool naturally to obtain.

[0033] Example 5 An in-situ doped cross-linked polyethylene insulation material, wherein the components and the amounts thereof are shown in Table 1, is prepared by the following steps: S1, adding low-density polyethylene to a BUSS reciprocating single-screw mixer, adding an antioxidant 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and a voltage stabilizer 4-hydroxythieno[3,2-c]pyridine from a side feed port, adding tetraethyl orthosilicate from a spray gun port 1, adding a catalyst di-n-octyltin dilaurate from a spray gun port 2, melt-mixing at 120° C., filtering through a three-layer dynamic filtration system of 300 mesh, 600 mesh, and 300 mesh, and then introducing into deionized water (conductivity 0.04 μS / cm) for granulation and centrifugal dehydration to obtain modified polyethylene particles; S2. Transfer the modified polyethylene particles to a heated drum device, react at 95°C for 2 hours, add a cross-linking agent DTBP and a scorch retarder N-cyclohexylthiophthalimide, perform osmotic absorption at 95°C for 3 hours, devolatilize, dry with a molecular sieve (control the water content within 100 ppm), and cool naturally to obtain.

[0034] Example 6 An in-situ doped cross-linked polyethylene insulation material, wherein the components and the amounts thereof are shown in Table 1, is prepared by the following steps: S1, adding low-density polyethylene to a BUSS reciprocating single-screw mixer, adding an antioxidant 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and a voltage stabilizer 4-hydroxythieno[3,2-c]pyridine from a side feed port, adding tetraethyl orthosilicate from a spray gun port 1, adding a catalyst di-n-octyltin dilaurate from a spray gun port 2, melt-mixing at 130° C., filtering through a three-layer dynamic filtration system of 300 mesh, 600 mesh, and 300 mesh, and then introducing the mixture into deionized water (conductivity 0.04 μS / cm) for granulation and centrifugal dehydration to obtain modified polyethylene particles; S2. Add modified polyethylene particles to a rotary drum device, react at 90°C for 2 hours, then add a cross-linking agent DTBP and a scorch retarder N-cyclohexylthiophthalimide, perform permeation absorption at 95°C for 3 hours, devolatilize, dry with molecular sieves (control the water content within 100 ppm), and cool naturally to obtain.

[0035] Comparative Example Comparative Example 1 An insulating material, which differs from Example 1 in that an equal amount of nano-silicon dioxide is used to replace tetraethyl orthosilicate, and no catalyst is added.

[0036] Nano-silicon dioxide was obtained from Nanjing Tianxing New Materials Co., Ltd., with the product number H10.

[0037] Comparative Example 2 An in-situ doped cross-linked polyethylene insulating material is different from Comparative Example 1 in that an equal amount of 4-hydroxythieno[3,2-c]pyridine is used instead of n-propylbenzoic acid, as shown in Table 1.

[0038] Comparative Example 3 An in-situ doped cross-linked polyethylene insulating material is different from Comparative Example 2 in that the amounts of the components are different, see Table 1 for details.

[0039] Comparative Example 4 An in-situ doped cross-linked polyethylene insulating material is different from Example 3 in that the amount of dioctyltin dilaurate added is different, see Table 1 for details.

[0040] Comparative Example 5 An in-situ doped cross-linked polyethylene insulating material is different from Example 3 in that the amount of 4-hydroxythieno[3,2-c]pyridine added is different, see Table 1 for details.

[0041] Table 1 Components and their weights in Examples 1-6 and Comparative Examples 1-3 Performance Testing The following performance tests were performed on the insulating materials prepared in the examples and comparative examples, and the test results are recorded in Table 2.

[0042] 1. Conventional physical and mechanical properties test shall be carried out in accordance with JB / T 10437-2004; 2. The space charge density test and electric field distortion rate test shall be carried out in accordance with the provisions of Appendix B of GB / T 31489.1-2015, PEA method, sample thickness is 0.30-0.50mm, applied field strength is 20kV / mm, and application time is 60 minutes.

[0043] 3. The DC breakdown strength test is carried out in accordance with the provisions of GB / T1408.2-2016. The electrode is a column-plate electrode with a diameter of 25 mm. The starting voltage is 0, and the voltage rise rate is no more than 3 kV / s from 6 kV to breakdown.

[0044] 4. Impurity content test shall be carried out in accordance with the provisions of Appendix B of JB / T 10437-2004.

[0045] Table 2 Performance test results Referring to Table 1 and Table 2, the difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses an equal amount of nano-silicon dioxide instead of tetraethyl orthosilicate, and the average space charge density of the prepared material (2.8 C / m 3 ) and 70℃ electric field distortion rate (40%) are significantly higher than those in Example 1 (2.1C / m 3 , 31%), and the 70°C DC breakdown strength (86 kV / mm) is also significantly lower than that of Example 1 (118 kV / mm).

[0046] The possible reason is that nano silicon dioxide is in the form of ultrafine powder, which is difficult to measure accurately and is easy to agglomerate and difficult to disperse. It is not ruled out that a small amount of it exists in the form of agglomerates, causing extremely fine physical defects (the impurity content test also shows that the number of impurities of 50-100 μm in Comparative Example 1 is 7). In Example 1, the good compatibility of tetraethyl orthosilicate and polyethylene is utilized to generate silicon dioxide by in-situ polymerization in the polyethylene material, thus avoiding the aggregation problem (the impurity content test also shows that the impurity content of 50-100 μm in Examples 1-6 is 0), and the effect of inhibiting space charge accumulation and improving DC breakdown strength is better.

[0047] Referring to Table 1 and Table 2, the difference between Example 2 and Example 1 is that in Example 2, an equal amount of 4-hydroxythieno[3,2-c]pyridine is used to replace the voltage stabilizer n-propylbenzoic acid, and the average space charge density and 70°C electric field distortion rate of the prepared material are reduced to 1.6 C / m 3 , 18%, and the DC breakdown strength at 70℃ increased to 139kV / mm, indicating that the effect of 4-hydroxythieno[3,2-c]pyridine is significantly better than that of n-propylbenzoic acid.

[0048] Analysis shows that the possible reason is that 4-hydroxythieno[3,2-c]pyridine has both 4-hydroxythiophene and pyridine groups, and can be tautomerized between enol and keto forms, which can homogenize the internal trap energy levels of cross-linked polyethylene, increase the trap density and control charge aggregation. It is also not easy to volatilize at high temperatures, which significantly improves the high-voltage breakdown strength and other properties of the material.

[0049] Furthermore, the difference between Comparative Example 2 and Comparative Example 1 is that in Comparative Example 2, the voltage stabilizer n-propylbenzoic acid is replaced with an equal amount of 4-hydroxythieno[3,2-c]pyridine. As a result, the DC breakdown strength of Comparative Example 2 (98 kV / mm) is also better than that of Comparative Example 1 (86 kV / mm).

[0050] In summary, by adding tetraethyl orthosilicate to generate silica-doped polyethylene through in-situ polymerization, the spatial charge accumulation in the cross-linked polyethylene insulating material under high electric field can be more effectively suppressed, thereby improving the DC breakdown strength of the cross-linked polyethylene; the newly discovered 4-hydroxythieno[3,2-c]pyridine is significantly superior to the currently commonly used voltage stabilizers, such as n-propylbenzoic acid, in improving the DC insulation performance of the material.

[0051] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An in-situ doped cross-linked polyethylene insulating material, characterized in that: The composition comprises the following components in parts by weight: 100 parts of low-density polyethylene, 1.5-2.0 parts of tetraethyl orthosilicate; 1.5-1.7 parts of cross-linking agent, 0.3 parts of antioxidant, 0.1 parts of scorch retarder, 0.02 parts of catalyst, 0.2-0.4 parts of voltage stabilizer.

2. The in-situ doped cross-linked polyethylene insulating material according to claim 1, characterized in that: The voltage stabilizer is 4-hydroxythieno[3,2-c]pyridine.

3. The in-situ doped cross-linked polyethylene insulating material according to claim 1, characterized in that: The density of low-density polyethylene is 0.920 g / cm 3 .

4. The in-situ doped cross-linked polyethylene insulation material according to claim 1, characterized in that: The cross-linking agent is one or both of dicumyl peroxide and di-tert-butyl peroxide.

5. The in-situ doped cross-linked polyethylene insulation material according to claim 1, characterized in that: The antioxidant is one or more of 2-propenoic acid-2-(1,1-dimethylethyl)-6-[[3-(1,1-dimethylethyl)-2-hydroxy-5-methylphenyl]methyl]-4-tolyl ester, 1,3,5-trimethyl-2,4,6,-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 2-{1-[2-hydroxy-3,5-bis(2-methylbutyl-2-yl)phenyl]ethyl}-4,6-di(2-methylbutyl-2-yl)phenyl acrylate, and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate.

6. The in-situ doped cross-linked polyethylene insulation material according to claim 1, characterized in that: The scorch retarder is one or more of N-cyclohexylthiophthalimide, N-phenyl-N-trichloromethylthiobenzenesulfonamide, and N-nitrosodiphenylamine.

7. The in-situ doped cross-linked polyethylene insulation material according to claim 1, characterized in that: The catalyst is one or two of dioctyltin dilaurate and bismuth neodecanoate.

8. The in-situ doped cross-linked polyethylene insulation material according to claim 7, characterized in that: The catalyst has a free chlorine content of 30 ppm.

9. A method for preparing an in-situ doped cross-linked polyethylene insulating material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Melt low-density polyethylene, antioxidant, voltage stabilizer, tetraethyl orthosilicate and catalyst at 120-140° C., filter, granulate in water, and dehydrate to obtain modified polyethylene particles; S2. The modified polyethylene particles are reacted at 90-98°C for 2-3h, and then a cross-linking agent and a scorch retarder are added, and the particles are subjected to permeation absorption at 95-98°C for 2-3h, and then devolatilized, dried with a molecular sieve, and cooled to obtain the product.

Citation Information

Cited By

  • Crosslinkable polyethylene insulation material and application thereof, crosslinked polyethylene insulation material and preparation method and application thereof

    CN121378977A